2015
DOI: 10.1353/hpn.2015.0123
|View full text |Cite
|
Sign up to set email alerts
|

How Native Do They Sound?: An Acoustic Analysis of the Spanish Vowels of Elementary Spanish Immersion Students

Abstract: Language immersion students’ lexical, syntactic, and pragmatic competencies are well documented, yet their phonological skill has remained relatively unexplored. This study investigates the Spanish vowel productions of a cross-sectional sample of 35 one-way Spanish immersion students. Learner productions were analyzed acoustically and compared to those of Spanish-English bilingual peers. Findings reveal that learners’ productions differ from those of their native Spanish-speaking peers on nearly all measures; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Other L2 studies have reported higher mean F1 values for Spanish vowels produced by L2 English learners in comparison to Spanish speakers (Menke, 2015;Ruiz Mella and Soto-Barba, 2005). Higher F1 values for L2 Spanish vowels could be explained in reference to the American English vowel system.…”
Section: Vowel Qualitymentioning
confidence: 83%
See 1 more Smart Citation
“…Other L2 studies have reported higher mean F1 values for Spanish vowels produced by L2 English learners in comparison to Spanish speakers (Menke, 2015;Ruiz Mella and Soto-Barba, 2005). Higher F1 values for L2 Spanish vowels could be explained in reference to the American English vowel system.…”
Section: Vowel Qualitymentioning
confidence: 83%
“…It is important to reiterate that we controlled for dialect variation by using only the data of L2 learners and native speakers from New York City and Mar del Plata, respectively, unlike other perception and production L2 and cross-linguistic studies (Cobb and Simonet, 2015;Escudero and Boersma, 2004;Menke, 2015;Menke and Face, 2010).…”
Section: Speakersmentioning
confidence: 99%
“… 4. These three studies (Menke, 2010; Menke & Face, 2010; Cobb & Simonet, 2015) also examine the effects of stress, especially with regard to the potential (more English-like) centralization of unstressed vowels. Because the present study examines only stressed vowels, the results regarding centralization are not reviewed here. …”
Section: Notesmentioning
confidence: 99%
“…Previous empirical work on L2 Spanish vowels has examined vowel quality, vowel quantity (i.e., duration), tendency to diphthongize, and differences in quality and quantity on the basis of stress context (e.g., Cobb & Simonet, 2015; Díaz & Simonet, 2015; Elliott, 1997; Menke, 2010; Menke & Face, 2010; Simoẽs, 1996). Given the focus of the present study, we restrict our review to those studies that explore development in L2 Spanish vowel quality and, more specifically, to those that employ acoustic measures to track production and development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation